In silico vaccine design: A tutorial in immunoinformatics - Dominic D. Martinelli (Healthcare Analytics, 2022)
Immunoinformatics, as a discipline, concerns the application of computational systems to study the immune system. Recently, the principles of reverse vaccinology have united with immunoinformatics to construct and evaluate novel vaccines in silico, enabling an economical response to emergent pathogens. In this tutorial, the basic procedure for in silico vaccine design is outlined. Because theoretical methods often suffer from a lack of transparency, limiting their practicality, this guide is written to minimize these discrepancies. Three concise phases – target selection and epitope identification, vaccine construction, and vaccine analysis and refinement – are detailed. To demonstrate, a simple vaccine against Plasmodium vivax is composed and validated. It exhibited a population coverage of 99.95% and favorable biophysical properties, making it a promising candidate for malaria prevention. This tutorial renders efficient in silico vaccine design accessible, introducing an opportunity to enhance the future of immunology.